Analyzing the Relationship Between Economic, Demographic, Legal and Institutional Variables Towards Tax Evasion Practice in Pontianak - Simanjaya, Felicia Kiki (Jurnal KIAFE, 2024)
This study aims to examine the effects of economic, demographic, and legal and institutional variables on tax evasion practices in Pontianak, West Kalimantan, Indonesia. This study employs a quantitative approach using multiple regression analysis. Data were collected through questionnaires distributed to 120 respondents, of which 100 respondents met the research criteria after the screening process. The economic variable was measured using income level and income source, the demographic variable was measured using age, gender, and education, while the legal and institutional variable was measured using trust in government and tax complexity. The results indicate that economic and legal and institutional variables have positive and significant effects on tax evasion practices, whereas the demographic variable has a negative and significant effect on tax evasion practices.